Pengembangan Sistem Deteksi Senyawa Sianogen dalam Ubi Kayu (Manihot esculenta Crantz) dengan Pendekatan Enzimatis - Sulistinah, Nunik; Riffiani, Rini; Sunarko, Bambang (JURNAL BIOLOGI INDONESIA, 2014)
Picrate paper test kit for the semiÃ¢â¬âquantitative determination of cyanogenic potential was developed in thisexperiment. The method is relatively simple, easy to use and might be applicable in the field by unskilled person.Paper test was attached on tubes containing sample (100 mg) in aquadest (0,5 mL) and then was immediatelycovered tightly and incubated overnight at room temperature. The colour of picrate paper test changed graduallytowards reddish brown, and its colour was compared with standart colour chart which included 0-800 ppm cyanidethat was also developed in this study. The reddish brown colour of paper test was correlated with cyanideconcentration on the sample. In order to obtain a more accurate detection of cyanogenic compound the paper testwas eluted with 5 mL water or aquadest and the absorbance was measured at 510 nm.Keywords: cyanogenic potential, picrate paper test, semi-quantitative method, simple method, cassava (Manihotesculenta Cranz)